PENGARUH PEMBERIAN PUPUK ORGANIK KOMPOS KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABE KERITING (Capsicum annum L) - Lukman Arif; Karmila Karmila (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
This study aims to determine the effect of cow manure compost on the growth and yield of curly chili plants (Capsicum annum L). This research was conducted using Randomized Block Design (RBD) consisting of 6 treatments and 3 replications so that there were 18 polybags. The results of the study, that the administration of cow manure at a dose of 1: 5 formed more productive branches and the highest yield with an average weight of 105.65g/tree